Relative importance of aneurysm diameter and body size for predicting abdominal aortic aneurysm rupture in men and women - Lo, Ruby C.; Lu, Bing; Fokkema, Margriet T.M.; Conrad, Mark; Patel, Virendra I.; Fillinger, Mark; Matyal, Robina; Schermerhorn, Marc L. (Journal of vascular surgery, 2014)
Women have been shown to have up to a fourfold higher risk of abdominal aortic aneurysm (AAA) rupture at any given aneurysm diameter compared with men, leading to recommendations to offer repair to women at lower diameter thresholds. Although this higher risk of rupture may simply reflect greater relative aortic dilatation in women who have smaller aortas to begin with, this has never been quantified. Our objective was therefore to quantify the relationship between rupture and aneurysm diameter relative to body size and determine whether a differential association between aneurysm diameter, body size, and rupture risk exists for men and women. We performed a retrospective review of all patients in the Vascular Study Group of New England (VSGNE) database who underwent endovascular or open AAA repair. Height and weight were used to calculate each patient's body mass index and body surface area (BSA). Next, indices of each measure of body size (height, weight, body mass index, BSA) relative to aneurysm diameter were calculated for each patient. To generate these indices, we divided aneurysm diameter (in cm) by the measure of body size; for example, aortic size index (ASI) = aneurysm diameter (cm)/BSA (m2). Along with other relevant clinical variables, we used these indices to construct different age-adjusted and multivariable-adjusted logistic regression models to determine predictors of ruptured repair vs elective repair. Models for men and women were developed separately, and different models were compared using the area under the curve. We identified 4045 patients (78% male) who underwent AAA repair (53% endovascular aortic aneurysm repairs). Women had significantly smaller diameter aneurysms, lower BSA, and higher BSA indices than men. For men, the variable that increased the odds of rupture the most was aneurysm diameter (area under the curve = 0.82). Men exhibited an increased rupture risk with increasing aneurysm diameter (<5.5 cm: odds ratio [OR], 1.0; 5.5-6.4 cm: OR, 0.9; 95% confidence interval [CI], 0.5-1.7; P = .771; 6.5-7.4 cm: OR, 3.9; 95% CI, 1.9-1.0; P < .001; ≥7.5 cm: OR, 11.3; 95% CI, 4.9-25.8; P < .001). In contrast, the variable most predictive of rupture in women was ASI (area under the curve = 0.81), with higher odds of rupture at a higher ASI (ASI >3.5-3.9: OR, 6.4; 95% CI, 1.7-24.1; P = .006; ASI ≥4.0: OR, 9.5; 95% CI, 2.3-39.4; P = .002). For women, aneurysm diameter was not a significant predictor of rupture after adjusting for ASI. Aneurysm diameter indexed to body size is the most important determinant of rupture for women, whereas aneurysm diameter alone is most predictive of rupture for men. Women with the largest diameter aneurysms and the smallest body sizes are at the greatest risk of rupture.